1852 Miss. Laws 328 - (:unkn) unknown (My University, 1852)
Act of Mar. 15, 1852, ch. 206: Prohibited issuing licenses to "negroes" to carry and use firearms.
Keywords: ENSLAVED PERSONS & OTHER MINORITIES